Anxiety of public speaking in English language among UUM Arab-students - Asmar, Mohammed Jamil (2009)
The primary aim of this study is to identify the problems that UUM Arab students face before and while giving a speech in public and then concentrate on the causes of anxiety. The second aim is to identify the strategies that UUM Arab students use to overcome public speaking anxiety. The findings of this study indicates that UUM Arab students have moderate anxiety while giving a speech in public and that the majority of Arab students feel anxious and tense when they try to speak in public. These results proved that Arab students have a lack experience in speaking English language in public which is due to the ignorance of speaking activities in the classroom language in the primary and secondary levels. This study has revealed a number of issues related to Arab students in terms of lack of experience, lack of self-confidence, tension, shyness, fear of negative evaluation, and losing face in public. These factors have negatively affected UUM Arab student's oral skills which were clearly seen in the findings of the questionnaire. Finally, UUM Arab students have revealed some practical strategies to overcome public speaking anxiety such as imitating worldwide broadcasters of CNN and BBC. They believe that in order to get rid of anxiety, they have to learn how to they deliver their speeches with high confidence and then learning the accurate spelling and ultimately pronunciation